INTIMATE PARTNER VIOLENCE DURING PREGNANCY AND ITS OUTCOME - Washdev . (Army Medical College Rawalpindi, 2018)
Objective: To determine the predictive relationship of violence by intimate partner specifically during pregnancy with stress, anxiety, depression in postnatal period. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at Jinnah Medical and Dental College (JMDC) Karachi, from Jan 2016 to Jun 2016. Material and Methods: Sample of present study consisted of 70 women between 18 to 40 years with mean age of 26.02 ± 5.5 years. Demographic information form, Karachi domestic violence scale, and depression, anxiety, stress scale were administered after 1 to 2 weeks of delivery. Results: The study identified that violence against women prevailed was found 32.9%. Regression analysis showed that violence against women during pregnancy has 23.4% variation in scores of depression, 17.5% variations in scores of anxiety domain, and 5.8% variation in scores of stress. Conclusion: Keeping in view the intimate partner violence prevalence against women during pregnancy and its adverse impact on the mental health of women, it is suggested to include screening program at perinatal clinics to identify at risk women to provide further clinical services to preclude negative outcomes.